Comparative Evaluation of Pulsed Versus Constant Exposure Patterns on the Acute Toxicity of 1,3,5—Trinitrobenzene to Daphnia magna - Eirkson, Charles E. III (My University, 1988)
The difference between the acute toxicities (72—hour EC50) of 1,3,5—trinitrobenzene (TNB) to Daphnia magna following pulsed and constant exposures was evaluated. Pulsed exposure means that daphnids were alternately exposed and not exposed to TNB for a predetermined period. Each period of exposure and nonexposure constituted one cycle period. Eight separate tests covering a selected range of exposure/nonexposure periods were conducted during the course of this research. Daphnids were exposed simultaneously to a range of three concentrations of TNB during pulsed or constant exposures in a specially designed flow—through test apparatus. The concentration of TNB which immobilized 50% of the daphnids (EC50) was estimated for the pulsed and constant exposures using probit or binomial statistical methods. In the two experiments where the TNB exposure period was less than 25% of the cycle period, the pulsed exposure EC5Os were significantly greater than the constant exposure EC5Os (p = 0.05). In the other six experiments where the period of exposure was 25% or greater, the difference between the pulsed and constant exposures were not significantly different, but in four of these six experiments, the EC5Os for the pulsed exposures were greater than the EC5Os resulting from the constant exposure. Additionally, of the four experiments where the concentration— immobilization slopes were available, two were statistically steeper for the pulsed exposures compared to the corresponding slopes for the constant exposures. The other two slopes were also steeper, but not to a statistically significant degree. The data demonstate that pulsed exposures to TNB are less toxic, especially when the period of exposure is short (less than 25% of a cycle). The data also indicate that the daphnids range of sensitivity to TNB may decrease when exposures occur as pulses.